Scalable QoS-based IP multicast over label-switching wireless ATM networks. - Won-Tae Kim
A Mobile IP multicast prototype that integrates a label-switching wireless asynchronous transfer mode, the mobile core-based multicast architecture, and an Internet multicast infrastructure is presented. MCOM creates multiple core-based layer 2 multicast trees that are independently established in member networks. They are interconnected via the Internet using layer 3 multicast routing. Gateways on the border of the Internet and wireless ATM networks convert ATM multicast traffic to suitable IP packets as well as converting from IP packets to ATM cells for MCOM. To solve the cell interleaving problem that results, ATM block transfer/immediate transmission capability is reasonably modified. Additionally, class-based block buffer management for ATM multicast connections is built into wireless ATM switches for soft quality of service control. Dynamic group management, multicast channel rerouting, and reliable multicasting are also studied in relation to existing Internet protocols like Mobile IP, Internet group management protocols, and multicast routing protocols
Keywords: ATM block transfer/immediate transmission; ATM cells; ATM multicast traffic; IP packets; Internet; Internet group management protocols; Internet multicast infrastructure; Internet protocols; MCOM; Mobile IP multicast prototype; Asynchronous transfer mode; Cell interleaving problem; Class-based block buffer management; Core-based layer 2 multicast trees; Dynamic group management; Gateways; Label-switching wireless ATM networks; Layer 3 multicast routing; Mobile core-based multicast architecture; Multicast channel rerouting; Multicast routing protocols; Quality of service control; Reliable multicasting; Scalable QoS-based IP multicast; Wireless ATM switches